Pengaruh Kebijakan Utang, Kepemilikan Institusional, Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan - Yuniar, Vira; Eka Kusuma Dewi (CV. ULIL ALBAB CORP, 2026)
This study aims to analyze the effect of debt policy, institutional ownership, and corporate social responsibility on firm value in manufacturing companies within the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the years 2019-2024. The variables are measured using Debt to Equity Ratio (DER) for debt policy, Institutional Ownership (IO) for institutional ownership, CSR score for corporate social responsibility, and Price to Book Value (PBV) for firm value. The sample was selected by purposive sampling, obtaining 38 companies, then 3 companies were excluded as outliers, resulting in 35 companies multiplied by 6 years, thus a total of 210 observations. The hypothesis testing was conducted using panel data regression with the assistance of EViews version 9. Debt policy, institutional ownership, and corporate social responsibility simultaneously have a positive and significant effect on firm value. Debt policy (X1) has a positive and significant effect on firm value. Institutional ownership (X2) has no effect on firm value. Corporate social responsibility (X3) has a positive and significant effect on firm value.